The effects of SNP and some plant hormones on Sunflower (Helianthus annuus L.) seedling leaves exposed to salt stress - Kirecci, Oguz Ayhan; Yurekli, Fusun; Yilmaz, Okkse (Progress in Nutrition, 2019)
In this study, the effects of salt stress, sodium nitoprusside (SNP) and hormones (Abscisic acid, Indol acetic acid and Gibberellic acid) applications on fatty acids concentrations of sunflower (Helianthus annuus L. cv. Tarsan-1018) plant leaf were investigated. Helianthus annuss L. cv. TARSAN - 1018 seeds were obtained through the Edirne Thrace Agricultural Research Institute, in Turkey. Following surface sterilization, the seeds were kept in water with aquarium pomp for 24 hours. The light intensity was 222 µmol / m2s on the leaf surface. Seeds were grown in 16 hours light, 8 hours dark photoperiod. Seeds were irrigated with Hoagland culture solution for 5 weeks. At the end of the fifth week salt, SNP and hormone applications were performed with foliar application for 72 hour. At the end of 72 hours samples were taken. Fatty acid composition of leaf tissues of sunflower (Helianthus annuus L. cv. Tarsan-1018) were determined by using gas chromatography. 300 mM salt application caused decrease concentrations of C16:0, C17:0, C18:1 and C18:3. 100 µM sodium nitoprusside has reduced the concentrations of C16:0, C17:0, C18:1. Hormone applications. adversely affected fatty acid concentrations. The results show that salt stress, sodium nitoprusside and hormone applications have negative effects on C16:0, C17:0, C18:1 and C18.3 concentrations in Tarsan-1018 sunflower leaf tissues.